Profiling cell-biomaterial interactions via cell-based fluororeporter imaging. (September 2007) - Treiser, Matthew D.; Liu, Er; Dubin, Robert A; Sung, Hak-Joon; Kohn, Joachim; Moghe, Prabhas V.
Cell-based, high-throughput screening has revolutionized the development of small-molecule pharmaceuticals. A similar paradigm for the accelerated development of biomaterials for cell and tissue engineering involves the iterative use of combinatorial biomaterial synthesis, rapid cellular response screens, and computational modeling methods. However, assays to probe cell responses to biomaterials are frequently subjective, lack dynamic responsiveness, and are limited to low-throughput experimentation. In this report, we highlight the use of high-resolution imaging of cell-based fluororeporters to establish and correlate quantifiable metrics of cell functional end points (e.g., cell growth, cell adhesion, cell attachment strength), as well as of intracellular cytoskeletal features (e.g., descriptors of actin organization) on a set of model biomaterial substrates synthesized by combinatorial variations. Selected mammalian cell lines were genetically engineered with a series of green fluorescent protein (GFP) fusion genes to allow for live cell imaging on biomaterials. We demonstrate that high-content imaging yields a large number of quantifiable morphometric descriptors of ultrastructural cell features (e.g., cell cytoskeleton) in conjunction with densitometric descriptors of cell behaviors (e.g., cell apoptosis). We illustrate how such descriptors can be used to discern combinatorial variations in substrate composition, and how living GFP reporters are uniquely suited to generate such descriptors unlike fixed tissue preparations. This quantitative approach of live fluororeporter cell imaging could be valuable for metrology of cell-material interactions.